In Vitro Ruminal Metagenomic Profiles and Ruminal Fermentation Variables of Aromatic Plant Pulps - Kanber Kara; Sena Yilmaz Öztaş; Erol Baytok (Veterinary Medicine and Science, 2025)
ABSTRACT Background Aromatic plant residues remaining after aromatic oil extraction represent a promising alternative feed source due to their rich bioactive compound content and fibrous structure. However, their fermentative behaviour and microbial degradability in the rumen require evaluation. Objective This study aimed to determine the nutrient composition, in vitro ruminal gas production, digestibility characteristics and fermentation end‐products of aromatic plant pulps (sage, thyme, lavender and yarrow) obtained via hydrodistillation. Methods Dried pulps were analysed for nutrient contents and subjected to in vitro ruminal fermentation for 24 h. Gas production estimated metabolizable energy (ME), net energy for lactation (NEL), organic matter digestibility (OMd), ammonia nitrogen (NH3‐N) and short‐chain fatty acid (SCFA) profiles were evaluated. Microbial community composition was assessed via 16S rRNA‐based metagenomics. Results Yarrow pulp had the highest gas production, ME, NEL, OMd and SCFA concentrations (AA, BA, IVA, T‐SCFA) (p < 0.05). Thyme pulp exhibited the highest NH3‐N levels (75.14 mg/L), suggesting high rumen‐degradable protein content. Sage pulp had the lowest NH3‐N levels (60.93 mg/L). Microbial composition shifted with fibre content; higher lignin (in lavender) was associated with lower Bacteroidota and higher Firmicutes abundance. Methanogenic archaea (Methanobrevibacter) were least abundant in thyme pulp (p < 0.05). Conclusion Due to their fermentability and favourable microbial responses, aromatic plant pulps, particularly yarrow, show promise as functional ruminant feed ingredients. These byproducts may enhance ruminal fibre utilization while modulating microbial ecology and reducing methane‐associated archaea.